Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1111/j.1467-8624.1998.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Relational Self-Worth: Differences in Perceived Worth as a Person across Interpersonal Contexts among Adolescents

Abstract: The present study investigated the hypothesis that in addition to perceptions of one's global self-worth as a person, individuals evaluate their self-worth differently across relational contexts. Perceptions of self-worth among adolescents were examined in 4 such contexts: with parents, teachers, male classmates, and female classmates. The factor pattern revealed a clear, 4-factor solution with negligible cross-loadings. Approximately three-fourths of the participants reported differences in self-worth, rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 20 publications
(27 reference statements)
4
39
0
1
Order By: Relevance
“…This model was not confirmed since no relationship was found between perception of family structure by parents, as expressed in the ideal vs. the actual version of FACES, and self-worth as appraised by their children. This finding is congruent with the those of Harter, Waters, and Whitesell (1998), who noted that there are other specific factors such as academic achievement, peer relations, and body image, which may be more relevant to adolescent children's sense of self-worth than family-related variables.…”
Section: Family Structure and Self-worthsupporting
confidence: 86%
“…This model was not confirmed since no relationship was found between perception of family structure by parents, as expressed in the ideal vs. the actual version of FACES, and self-worth as appraised by their children. This finding is congruent with the those of Harter, Waters, and Whitesell (1998), who noted that there are other specific factors such as academic achievement, peer relations, and body image, which may be more relevant to adolescent children's sense of self-worth than family-related variables.…”
Section: Family Structure and Self-worthsupporting
confidence: 86%
“…Therefore, it is not surprising that Pfeifer et al (2007) found greater MPFC activity for children than for adults when contrasting ratings for self with ratings for a well-known fictional character (i.e., Harry Potter). Likewise, in line with the theory that adolescence is marked by a heightened preoccupation with others' opinions about oneself and that these perceived opinions help inform the adolescent's self-concept (Harter 1999, Harter et al 1998), Pfeifer and colleagues (2009) found that, relative to mature adults, adolescents engage brain areas related to social cognition (see Theory of Mind section below for a description of these regions) during self-reflection in addition to MPFC and posterior cingulate cortex. Replicating their prior finding (Pfeifer et al 2007), brain activity was once again greater in self-relevant regions for adolescents than for adults.…”
Section: Self-awareness and Self-knowledgementioning
confidence: 59%
“…This approach was based on a single-item adaptation of Rosenberg's self-esteem scale (Robins and others 2001). Veterinary scenarios were added because of the potential for situational variability in confidence and self-esteem (Harter and others 1998); by providing context, it was intended that measurements of these parameters would relate to confidence and self-esteem specifically in the veterinary workplace. For assessment of confidence, participants were asked to imagine they were in a veterinary environment and were requested to perform a task they had never done before.…”
Section: Methodsmentioning
confidence: 99%